Impact of Intra-European Trade Agreements, 1990-2005 : Policy Implications for the Western Balkans and Ukraine - Qiao, Zhaogang; Herderschee, Johannes (Washington, D.C. : International Monetary Fund, 2007)
The paper provides quantitative estimates of the impact of the European trade agreements on trade flows. It applies both static and dynamic panel estimation techniques. The results are useful to policymakers because new intra-European trade agreements are being negotiated. In the absence of a further expansion of the European Union, estimates of alternative policies may help to clarify the policy debate. The paper also illustrates that the performance of individual countries under the trade agreements can be explained in terms of their macroeconomic environment. The conclusions are likely to be relevant to the western Balkan countries and Ukraine.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet